Standardized nursing languages in orthopedics from the perspective of the nursing role effectiveness model - Marcos Barragan da Silva; Bruna Engelman; Manoela Schmarczek Figueiredo; Miriam de Abreu Almeida (Universidade Federal do Rio Grande do Sul, 2022)
ABSTRACT Objective To analyze the standardized nursing languages in orthopedics from the perspective of the Nursing Role Effectiveness Model. Method Mixed method research carried out in a hospital in southern Brazil between April 2016 and February 2017. Quantitative data were collected from 85 orthopedic patients using the NANDA-International, Nursing Interventions and Outcomes, and submitted to statistical analysis. Qualitative data were collected through interviews with 10 nurses and were analyzed using content analysis. Results Acute pain (96%) was a prevalent nursing diagnosis. Fall Prevention (33.3%) was the most prescribed intervention. Pain Level, Body Positioning: self-initiated and Mobility showed an increase in outcome scores (p<0.001). In the interviews, nurses indicated that priority diagnoses and nursing interventions contributed to improving mobility outcomes. Conclusion The findings revealed that the focus of Standardized Nursing Languages in orthopedics from the perspective of the Nursing Role Effectiveness Model lies in the context of mobility, but it needs improvements in diagnostic accuracy and electronic health record.